Die Markuspassion: eine antike Tragödie - Lescow, Theodor (Biblische Notizen, 2005)
As a closed drama, Mark’s passion narrative was modelled on ancient tra-gedy. Hence, it is fiction, thus being the perfect means for conveying the truth of what happened to future generations. As in ancient tragedy only one or two characters need to be historical, it may be assumed that Judas also belonged to the characters invented by Mark.